Evolutionary Mechanism of Government Green Development Behavior in Construction and Demolition Waste Recycling Projects: A Perspective of Ecological Compensation - Weihong Chen; Wenjun Yin; Beiyu Yi; Shiqi Xu; Hao Zhang; Xingwei Li (Buildings, 2023)
Although construction and demolition waste (CDW) recycling projects have received increasing attention from national and regional governments, the mechanisms for the evolution of government green development behavior in such projects are not yet clear. From the perspective of ecological compensation for the cross-regional disposal of CDW, this study aims to reveal the evolutionary mechanism of government green development behavior through externality theory. The main findings are as follows. First, the initial probability of government adoption of green development behavior does not affect the final stable state of the system. Second, there is heterogeneity in the effects of the allocation coefficient of ecological benefits and the ecological compensation coefficient on different government green development behavior. Finally, ecological benefits can encourage the government to actively adopt green development behavior. This study introduces for the first time an ecological compensation perspective into the study of CDW project management, which not only enriches the knowledge system of the government green development behavior on project management but also provides a reference for the government to participate in the process of cross-regional disposal of CDW in favor of ecological compensation.